The interactional emergence of conditional clauses as directives: constructions, trajectories and sequences of actions. - Lindström, Jan; Lindholm, Camilla; Laury, Ritva (Language Sciences, 2016)
This article concerns the sequential emergence of Finnish and Swedish insubordinated jos and om ‘if’ adverbial clauses in interaction from a synchronic, online use perspective. The authors first demonstrate that such clauses function as complete directives without any main clauses, and that recipients treat them as such, responding to the directive as soon as the insubordinate clause is produced. It is then shown that many insubordinated conditionals used as directives (ICDs) are associated with a certain orderly sequential pattern organized in adjacency pairs, which bears a certain similarity to bona fide conditional clauses. This suggests that conditional clause patterns, including insubordinated ones, emerge in interaction in response to actions done and not done by the recipients of the requests, and are thus a product of the interaction of participants in conversation.